INTEGRASI NILAI-NILAI PENDIDIKAN LINGKUNGAN ISLAM DALAM PROSES PEMBELAJARAN DI MTS NEGERI 2 BANDAR LAMPUNG - Faqihuddin Akbar Mu’allim; Mu’adz Haidar Zulkarnain; Imam Syafei; Baharudin; Ali Murtadho (STKIP Subang, 2025)
This study aims to analyze the integration of Islamic environmental education values in the learning process at MTs Negeri 2 Bandar Lampung. The research employed a qualitative descriptive-analytical approach. Data were collected through observation, interviews, and documentation involving the principal, teachers, and students. The findings reveal that Islamic environmental education is not implemented as a separate subject but is integrated into classroom learning, teachers’ role modeling, and school culture through various programs and habitual practices. Value integration is carried out through value-oriented lesson planning, contextual learning that links subject matter with environmental realities, and the evaluation of students’ attitudes and behaviors. Teachers’ exemplary conduct plays a key role in internalizing environmental care values based on Islamic teachings. In addition, cleanliness programs, classroom environmental management, and the use of the school environment as a learning resource strengthen students’ ecological awareness. Supporting factors include the alignment of Islamic values with environmental conservation principles and a supportive school culture. Meanwhile, inhibiting factors consist of limited conceptual understanding among some educators and time constraints in the learning process.